The influences of cultural orientation, ecological awareness, price and psychological wellbeing over senior citizens’ green sheltered housing buying intentions - Oirik Menahem, Hanna; Boxer, Israel; Rekettye, Gábor (Marketing & Menedzsment, 2019)
The motivation for this research was to examine whether the „green trend” has a distinct added value from a marketing point of view. The research aimed at examining the effect of cultural orientation, price perception and ecological awareness, with the mediating effect of psychological wellbeing, over elderly people's intentions to buy accommodations in a green sheltered housing project. Results suggest that ecological awareness is the main factor influencing green sheltered housing buying intentions of elderly people, and that negative cultural orientation, such as collectivism and conservatism, decrease elderly consumers' buying intentions.